Editorial - Rodrigues Almeida, Carla; Frion, Emmanuel; Delgado, Paola C. M.; Miranda, Tays (Cadernos de Astronomia, 2024)
Editorial informations, with Letter to the Reader and Summary of the Special Edition dedicated to the event As Astrocientistas.